Utilization of the Hall Effect to Detect Leakage Current in DC System Branch Loads Using the Positive-Negative Current Difference Method - Kamal, Ahmad Ilham; Dona, Nur Rahma (Universitas Sultan Ageng Tirtayasa, 2024)
Currently, many industries use DC power as a power supply for controller equipment, etc. All companies want their DC system to be reliable. One effort to maintain the reliability of the DC system is to monitor the leakage current in each branch of the DC system load. Leakage currents that occur if not discovered early on will gradually result in short circuit currents and instability of the DC system. This research wants to use the hall effect to detect leakage currents in branch loads using the difference in current in the positive (+) and negative (-) cables. Use the right-hand law for the direction of the magnetic field. Insert the positive (+) and negative (-) cables into the same Hall sensor where the resultant magnetic field will be 0 under normal circumstances and >0 or <0 if there is a leakage current in one of the cables. Because of this, the Hall effect can be used to detect leakage currents (Ground Fault) in DC systems. Another advantage of the Hall effect is that it monitors DC system leakage currents continuously while operating.